Organoleptic Quality Formulation of Soybean Sprouts Milk (Glycine max) and Jawawut (Setaria italica) as a Pregnant Women’s Supplementary Feeding Drink - Maryam Razak (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
ABSTRACT Background: Riskesdas data in 2018, the prevalence of pregnant women KEK in Indonesia is 17.3%. Meanwhile, the prevalence of anemia pregnant women in Indonesia has increased compared to 2013, which was 37.1% and in 2018 it was 48.9%. Efforts to overcome the impact of malnutrition in pregnant women can be through interventions by supplementary feeding to pregnant women. Supplementary feeding is already included in the intervention program that has been established by the Indonesian Ministry of Health for pregnant women KEK in the form of biscuits. Based on the evaluation of the Ministry of Health 2017, the implementation of the supplementary feeding has experienced problems with the compliance of pregnant women with supplementary feeding consumption, namely that most pregnant women cannot finish all the supplementary feeding biscuits received. For this reason, an alternative supplementary feeding is used to overcome this problem in the form of vegetable milk drinks from soybean sprouts and millet seeds which are local food ingredients. Objective: This study aims to analyze the effect of millet formulation on soybean sprouts milk as PMT for pregnant women on the organoleptic quality of color, flavour, and taste. Methods: This study used a completely randomized design (CRD) consisting of 4 levels of treatment, namely P1 (100: 0), P2 (60:40), P3 (50:50), P4 (40:60) observations were made on the organoleptic quality of the color, flavour, and taste. Results: The results showed that the organoleptic quality (color, flavour, taste) - on average, respondents like it. Kruskal Wallis statistical test showed a significant effect on color, flavour and taste. The best treatment was P2 (60:40) and the fulfillment of RDA for pregnant women in the first trimester was 87.8% energy, 121.6% protein, 97.9% carbohydrates, 66.4% fat and 49.2% iron.